DIGITALIZATION OF EDUCATION IN AZERBAIJAN - Nushaba Aslan Hajiyeva; Ragif Tofig Huseynov; Mehriban Rovsen Huseynova; Ayshan Viladdin Mammadova; Seymur Jeyhun Mammadov (Agora International Journal of Economical Sciences (AIJES), 2023)
In the 21st century, in the conditions of information abundance, management, that is, management of education, which is the basis of the state, society, and all economic development, is the most important issue. In modern times, all educational institutions are exposed to digital globalization in one way or another. Given the rapid development of information and the number of educational institutions due to high development and increase in student knowledge, technology increases the need for constant updating. Accelerating the implementation of digitization in the field of education in Azerbaijan is considered one of the urgent issues. In this situation, it is important to establish a mutual relationship in the field of globalization education, which has a mutual goal, to help the schools and universities of Azerbaijan. In this process, it is necessary to apply information technologies related to the use of changes, modern information and communication technology tools, databases, and provision with modern telecommunication tools at all stages of the digitization process of education and in the training content. The article analyzes the main directions of the application of digitization in education in Azerbaijan and shows the characteristics of the digital educational environment.
Keywords: 330